Ramalin, a Novel Phenyl Hydrazide from the Lichen Ramalina Terebrata; Isolation, Total Synthesis and Biological Activities - pandey, Durga Prasad; Bhattarai, Hari Datta (Tribhuvan University Journal, 2016)
Ramalin, a new L-glutamic acid derivative of phenylhydrazide (Y-glutamyl-N’-(2-hydroxyphenyl) hydrazide, 1) was isolated from the Antarctic lichen, Ramalina terebrata after a series of bioactivity guided fractionation of crude aqueous methanolic extract. Ramalin showed stronger antioxidant activities than commercially available standards, ascorbic acid, trolox, BHA, kojic acid in both, in vitro and in vivo test systems. In addition, ramalin showed no/less toxicity effects against two human cell lines; fibroblast (CCD-986SK) cells and keratinocyte (HaCaT). Thus, realign merits for cosmetic application and industrial scale production were needed. We developed a cost effective total synthesis of ramalin with 71.5% yield and described here.